High-content screening imaging and real-time cellular impedance monitoring for the assessment of chemical's bio-activation with regards hepatotoxicity. Issue 7 (October 2015) - Peyre, Ludovic; de Sousa, Georges; Barcellini-Couget, Sylvie; Luzy, Anne-Pascale; Zucchini-Pascal, Nathalie; Rahmani, Roger
Highlights Neutral red uptake was the most robust assay used for the drug cytotoxicity evaluation on murine liver models. Real-time cellular impedance could detect bio-activation through revealing specific curve profiles and response kinetics. Real-time cellular impedance seems unsuitable for use in monitoring viability in primary cultures of rat hepatocytes. The contribution of HCS appears necessary to highlight disruptions to cellular function in response to drug exposure. Coupling neutral red assay, real-time cellular impedance and HCS represents a complementary strategy for drug assessment.